Performance of rubella suspect case definition: implications for surveillance Acurácia da definição de caso suspeito de rubéola: implicações para vigilância - Solange Artimos de Oliveira; Luiz Antonio Bastos Camacho; Antonio Carlos de Medeiros Pereira; Marília Mattos Bulhões; Angélica Fortes Aguas; Marilda Mendonça Siqueira (Universidade de São Paulo, 2006)
OBJECTIVE: To assess the performance of the rubella suspect case definition among patients with rash diseases seen at primary care units. METHODS: From January 1994 to December 2002, patients with acute rash, with or without fever, were seen at two large primary health care units and at a public general hospital in the municipality of Niterói, metropolitan area of Rio de Janeiro, Brazil. Data from clinical and serologic assessment were used to estimate the positive predictive values of the definition of rubella suspect case from the Brazilian Ministry of Health and other combination of signs/symptoms taking serologic status as the reference. Serum samples were tested for anti-rubella virus IgM using commercially available enzyme immunoassays. Positive predictive values and respective 95% confidence intervals were calculated. RESULTS: A total of 1,186 patients with an illness characterized by variable combinations of rash with fever, arthropathy and lymphadenopathy were studied. Patients with rash, regardless of other signs and symptoms, had 8.8% likelihood of being IgM-positive for rubella. The Brazilian suspect case definition (fever and lymphadenopathy in addition to rash) had low predictive value (13.5%). This case definition would correctly identify 42.3% of the IgM-positive cases, and misclassify 26.1% of the IgM-negative cases. CONCLUSIONS: These results support the recommendation to investigate and collect clinical specimens for laboratory diagnosis of all cases of rash, for surveillance purposes. Although this strategy may increase costs, the benefits of interrupting the circulation of rubella virus and preventing the occurrence of congenital rubella syndrome should pay off. OBJETIVO: Avaliar a acurácia da definição de caso suspeito de rubéola entre pacientes com doenças exantemáticas atendidos em unidades de saúde pública. MÉTODOS: A população de estudo foi constituída de pacientes com doença exantemática, com ou sem febre, atendidos em serviços de saúde pública, de janeiro de 1994 a dezembro de 2002 no município de Niterói, RJ. Dados clínicos e sorológicos foram utilizados para estimar os valores preditivos positivos da definição de caso suspeito de rubéola do Ministério da Saúde do Brasil e outras combinações de sinais e sintomas, considerando o resultado da sorologia como referência. A detecção de IgM específica para rubéola em amostras sangüíneas foi realizada por ensaio imunoenzimático. Foram calculados os valores preditivos positivos e respectivos intervalos de confiança de 95%. RESULTADOS: Foram estudados 1.186 pacientes com uma doença caracterizada por uma variada combinação de rash com ou sem febre, artropatia e linfoadenopatia. Pacientes com exantema, independentemente da presença de outros sinais e sintomas, apresentaram uma probabilidade de 8,8% de serem IgM positivos para rubéola. A definição de caso suspeito de rubéola utilizada no Brasil apresentou baixo valor preditivo positivo (13,5%). Esta definição de caso identificou corretamente 42,3% dos casos IgM positivos, e classificou de forma incorreta 26,1% dos IgM negativos. CONCLUSÕES: Os resultados indicam que as doenças exantemáticas devem ser investigadas em conjunto para fins de vigilância epidemiológica e coleta de espécimens clínicos para o diagnóstico laboratorial. Esta estratégia aumenta os custos, mas gera benefícios na interrupção da circulação do vírus e na prevenção da síndrome da rubéola congênita.